Internationalizing the Business School: A Global Survey in 2000 - Kwok, Chuck C. Y.; Arpan, Jeffrey S. (Journal of International Business Studies, 2002)
We summarize the major findings of the sixth global survey of business school internationalization sponsored by the Academy of International Business (AIB). The survey covers various aspects of internationalization including: objectives, organizational issues, curriculum and faculty internationalization, foreign institutional arrangements, and satisfaction with progress achieved. The empirical results indicate that, across all dimensions, significant progress continued to be made in the internationalization of business schools.